2011
DOI: 10.1074/jbc.m110.150847
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine Oxidoreductase Promotes the Inflammatory State of Mononuclear Phagocytes through Effects on Chemokine Expression, Peroxisome Proliferator-activated Receptor-γ Sumoylation, and HIF-1α

Abstract: The protective effects of pharmacological inhibitors of xanthine oxidoreductase (XOR) have implicated XOR in many inflammatory diseases. Nonetheless, the role played by XOR during inflammation is poorly understood. We previously observed that inhibition of XOR within the inflammatory mononuclear phagocytes (MNP) prevented neutrophil recruitment during adoptive transfer demonstrating the role of XOR in MNP-mediated neutrophil recruitment. To further explore the role of XOR in the inflammatory state of MNP, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 90 publications
2
33
0
1
Order By: Relevance
“…XO increased Egr-1 mRNA and protein, as well as the phosphorylation of ERK1/2, while pretreatment with an ERK1/2 inhibitor prevented induction of Egr-1 by XO [78]. In addition, XO reportedly reduced SUMOylation of PPAR γ in inflammatory cells [79]. ROS from XO augment TRB3 expression in podocytes [80].…”
Section: Inflammation Occurrence Related To Ua Metabolismmentioning
confidence: 99%
“…XO increased Egr-1 mRNA and protein, as well as the phosphorylation of ERK1/2, while pretreatment with an ERK1/2 inhibitor prevented induction of Egr-1 by XO [78]. In addition, XO reportedly reduced SUMOylation of PPAR γ in inflammatory cells [79]. ROS from XO augment TRB3 expression in podocytes [80].…”
Section: Inflammation Occurrence Related To Ua Metabolismmentioning
confidence: 99%
“…54 Moreover, oxonate potentially modulates renal transport of UA, and thereby could affect intracellular handling and effects of UA in renal proximal tubular cells. 55 Hence, some mechanisms of renal disease in the in vivo model of oxonic acid-induced hyperuricemia remain to be resolved; ideally, an alternative model of hyperuricemia would help in this task.…”
Section: Recent Changes In Thinking About Ua and Xo Actions Pertinentmentioning
confidence: 99%
“…Several interventional studies have proven the efficacy of hyperuricemia treatments. A randomized controlled study showed that allopurinol prolongs exercise capacity trophil chemoattractant secretion from mononuclear phagocytes is reduced, and small ubiquitin-like modifier of PPARγ and hypoxia-inducible factor 1α levels are increased [92] . Febuxostat activates mitogen-activated protein kinase phosphatase-1 and inhibits inflammation by lipopolysaccharide stimulation through the inhibition of ROS generation [93] .…”
Section: Macrovascular Complicationmentioning
confidence: 99%